Knowledge, Attitude and Practice towards Human Immunodeficiency Virus Infection among University Freshmen Students Year 2016/2017 - Hervina Agustinawaty; Bony Wiem Lestari; Rudi Wisaksana (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Human Immunodeficiency Virus (HIV) infection is one of the most serious public health and social problems in the world. Transmission of HIV occurs in the age group of 20 years or below. One of the ways to prevent HIV transmission is to improve the knowledge so the attitude and practice can be changed. The objectives of this study was to identify the knowledge, attitude, and practice of HIV infection among university freshmen students year 2016/2017.Methods: This was a descriptive cross sectional quantitative study. Samples were selected using proportional random sampling and primary data were collected using questionnaires which were self-completed by 122 Universitas Padjadjaran freshmen students year 2016/2017 in November 2016. Questionnaire consisted of sociodemographic, knowledge, attitude, and practice data regarding to HIV infection. The collected data was analyzed dan presented in the form of tables and figure.Results: Respondents had a median age criterion of 18 years, 52.5% were female, 73.8% high school originated outside Bandung and 19.4% knew information about HIV/AIDS through the internet. There were 18.9% of the respondents classified as having “Good” knowledge, 63.9% classified as “Satisfactory” and the other 17.2% were classified as having “Poor” knowledge of HIV. There were 52.5% respondents who had negative attitude towards HIV discussion and 96.7% of the respondents had good practice.Conclusions: Lack of knowledge and negative attitude towards HIV infection and the presence of high risk practice for HIV infection demanded that students should receive reproduction health education to support the prevention of HIV infection.